Prescriber Compliance With Liver Monitoring Guidelines for Pazopanib in the Postapproval Setting: Results From a Distributed Research Network. Issue 1 (March 2019) - Shantakumar, Sumitra; Nordstrom, Beth L.; Hall, Susan A.; Djousse, Luc; van Herk-Sukel, Myrthe P.P.; Fraeman, Kathy H.; Gagnon, David R.; Chagin, Karen; Nelson, Jeanenne J.
Abstract : Objectives: Pazopanib received US Food and Drug Administration approval in 2009 for advanced renal cell carcinoma. During clinical development, liver chemistry abnormalities and adverse hepatic events were observed, leading to a boxed warning for hepatotoxicity and detailed label prescriber guidelines for liver monitoring. As part of postapproval regulatory commitments, a cohort study was conducted to assess prescriber compliance with liver monitoring guidelines. Methods: Over a 4-year period, a distributed network approach was used across 3 databases: US Veterans Affairs Healthcare System, a US outpatient oncology community practice database, and the Dutch PHARMO Database Network. Measures of prescriber compliance were designed using the original pazopanib label guidelines for liver monitoring. Results: Results from the VA (n = 288) and oncology databases (n = 283) indicate that prescriber liver chemistry monitoring was less than 100%: 73% to 74% compliance with baseline testing and 37% to 39% compliance with testing every 4 weeks. Compliance was highest near drug initiation and decreased over time. Among patients who should have had weekly testing, the compliance was 56% in both databases. The more serious elevations examined, including combinations of liver enzyme elevations meeting the laboratory definition of Hy's law were infrequent but always led to appropriate discontinuation of pazopanib. Only 4 patients were identified for analysis in the Dutch database; none had recorded baseline testing. Conclusions: In this population-based study, prescriber compliance was reasonable near pazopanib initiation but low during subsequent weeks of treatment. This study provides information from real-world community practice settings and offers feedback to regulators on the effectiveness of label monitoring guidelines.